A música no ambiente hospitalar: uma experiência de humanização - Souza, Luanda Oliveira [UNIFESP] (2019)
Introduction: Soundscape Studies – defined as any field of acoustic study - aims to analyse how the acoustic environment composed of sounds and noises, influences humans both directly or indirectly. The hospital environment are considered as unpleasant for most of the population, and this is because the treatment form is more associated to the disease than to the subjective aspects of the hospitalized person. In addition, the scientific and technological development of the health field, despite improving medical treatments, culminated in a more distant relationship between the patient and health care professional, turning hospitals into dehumanizing places. Music is an art form that has influenced human being since the dawn of civilization, developed individually or collectively and present practically in almost all cultures. Objective: to investigate the extent to which live music, by modifying the soundscape of that environment, can be a means to make the hospital a more humanized environment. Methodology: in partnership with Saracura Group, participant observation based in ethnographic approach was carried out in the following hospitals: Instituto da Criança do Hospital das Clínicas FMUSP, HCor – Hospital do Coração e Hospital Infantil Sabará, , which enabled the elaboration of field diaries with perceptions related to the modifications of the soundscape and the reactions of people to musical art. After this phase, Oral History of Life method interviews were made with two patients, four patient’s mothers, four health care professionals and two musicians, and the resulting stories were transformed into narratives. The data analyses were based on the narratives and field diaries by the qualitative method of Immersion / Crystallization inspired by the hermeneutic phenomenology. Results: from the collected data the emerged themes were: increase of affectivity visualized in mothers of neonatal patients through lullabies; music tones made the environment more harmonious, assisting patients in serious condition and companions in the complex issue of finitude, the music comforts the situation experienced, reassuring the patient and helping in farewells; and the possibility that the performing musician in hospitals can resignify after having counted on the pain and suffering of the other person. We identified that the hospital soundscape, endowed with noises, alarms and conversations, is harmonized by the music, so that all those involved get rid of the focus on the disease, opening space to experience music. We analysed that melodies were considered audible emotions, so that fundamental elemental properties such as time, space and movement were related to subjective aspects experienced in the hospital. Final considerations: The results indicate that music is one of the few artistic resources that do not spoil the work of health professionals, especially in the ICU, and also collaborates to provide a more serene, comfortable and joyful sector. In this way, themes such as affectivity, human finitude, and expanding of dialogue were discussed from changes in the hospital through live music. Thus, we conclude that musical actions can be a form of hospital humanization.